In Vivo Studies on the Inhibition of Coagulation by Fractionated Heparin and by a Heparin Analogue II. Effects of a Heparin Analogue - Schmitz-Huebner, U; Asbeck, F; Loo, J van de (Thrombosis and Haemostasis, 1981)
SSHA, a semi-synthetic heparin analogue, and sodium heparin from porcine intestinal mucosa were injected subcutaneously into six healthy volunteers over a period of three days in a cross-over trial. Before injection and 2, 4, 6, 8 hrs afterwards, the heparin like activity was measured with the APTT, the anti-Xa clotting test and two chromogenic substrate assays. The results show that SSHA mediates both anti-Xa and antithrombin activities in vivo. A comparison between the effects of SSHA and heparin is problematical due to the heterogeneity of different heparin preparations. Low doses of the analogue (45 mg s. c.) induced proportionally higher and longer lasting anti-Xa activities than higher doses (90 mg s. c.). Repeated injections of SSHA twice daily led to increasing effects on two tests for heparin-like activity, whereas two other tests remained unchanged. Both drugs were tolerated equally well, side effects were not detected. Clinical studies are required to demonstrate whether SSHA is similar or superior to low-dose heparin for use in thrombosis prophylaxis.
Keywords: Heparin analogue; Heparin; Thrombosis prophylaxis